Chemical bath deposition of nickel sulphide (Ni4S3) thin films - Kassim, Anuar; Nagalingam, Saravanan; Tan, Wee Tee; Ho, Soon Min; Teo, Darren (AcademicDirect, 2010)
Thin films of nickel sulphide were deposited from aqueous baths on indium tin oxide glass substrate. The chemical bath contained nickel sulphate, sodium thiosulfate and triethanolamine solutions. The aim of the present study was to analyze the different experimental conditions to prepare Ni4S3 thin films using chemical bath deposition technique. The structural, morphological and optical properties of nickel sulphide thin films were obtained by X-ray diffraction, atomic force microscopy and UV-Vis Spectrophotometer will be presented. The properties of the films varied with the variation in the deposition parameters. The films deposited at longer deposition time using lower concentration in more acidic medium showed improved crystallinity, good uniformity and better adhesion to the substrate. Films showed band gap of 0.35 eV and exhibited p-type semiconductor behaviour.